Effectiveness of Case-Based and Project-Based Learning in Promoting Sustainability Awareness: A Comparative Study - Khusnul Khotimah; Mochamad Kamil Budiarto; Arsyananda Rabbani; Leni Marpelina; Leo Andrew B. Biclar (Journal of Education Technology, 2025)
History learning, which is still dominated by conventional methods, tends to focus only on the cognitive aspect and has not fully addressed the affective and conative dimensions that are crucial in fostering students’ ecological awareness. This study aims to analyze the effectiveness of case-based learning and project-based learning in enhancing students’ ecological awareness. The research employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The study involved 89 students divided into two experimental groups. The data collection instrument was a Likert scale constructed based on three dimensions of ecological awareness: cognitive, affective, and conative. Data analysis was conducted using parametric statistical tests. The findings indicate that both learning approaches significantly improved students’ ecological awareness (p < 0.05). The case-based learning group achieved an average increase of 7.11 points (20.5%), while the project-based learning group increased by 4.93 points (14.4%). The posttest difference between the two groups was also significant (t = 3.365; p = 0.001), demonstrating the superiority of case-based learning in strengthening ecological awareness. These results confirm that the integration of context-based learning approaches in history education has the potential to strengthen the role of higher education in shaping a generation that excels not only academically but also in terms of care and responsibility for environmental sustainability. The implications of this research suggest that lecturers need to adopt innovative learning models that balance cognitive, affective, and conative aspects to support sustainable education and encourage the emergence of more responsive pedagogical practices to global challenges.